Superior Mesenteric Artery Syndrome with Esophageal Perforation: A Case Report - Tajima, Takayuki; Tanaka, Hikaru; Ogoshi, Kyoji; Shimada, Hideo; Chino, Osamu; Kise, Yoshifumi; Kenmochi, Takahiro; Nishi, Takayuki; Makuuchi, Hiroyasu (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2004)
A 16-year-old male visited his local doctor with the complaint of vomiting. Since investigations suggestedacute circulatory failure and acute renal failure, he was referred to our hospital. Plain X-ray films showedsubcutaneous emphysema extending from the neck to the precordial region, as well as marked dilation ofthe stomach and duodenal bulb. Chest CT showed subcutaneous emphysema of the precordial region andmediastinal emphysema. Abdominal CT showed dilation of the duodenum and stomach, indicating a doublebubble sign in the broad sense. Endoscopy revealed a 3 cm long esophageal perforation extending from themid portion of the esophagus to the left wall of the lower esophagus. An upper gastrointestinal contraststudy revealed dilation and obstruction of the horizontal part of the duodenum. Accordingly, he wasdiagnosed as having an esophageal rupture localized to the mediastinum, which was possibly induced by thesuperior mesenteric artery syndrome. He recovered with conservative therapy. This paper presents thedetails of this patient along with examination of previously reported cases.